Construction of zero correlation zone Gaussian integer sequence set - Yu-bo LI; Jia-an SUN; Nan JING (Tongxin xuebao)
The construction of zero correlation zone (ZCZ) Gaussian integer sequence set was researched.Based on binary orthogonal matrices,ZCZ ternary sequence sets were constructed by adding zeros at first.Then the ternary ZCZ squences were transformed into Gaussian integer sequences by using a perfect Gaussian integer sequence without changing the ideal autocorrelation functions and crosscorrelation functions in the zero correlation zone.The proposed ZCZ Gaussian integer sequence sets are optimal or almost optimal with respect to the Tang-Fan-Matsufuji bound.